Resiliensi Mantan Pekerja Tetap Pasca Penutupan Tambang Batubara di Embalut - Kiki Sabrina; Silverius Djuni Prihatin (Sasdaya: Gadjah Mada Journal of Humanities, 2025)
The closure of mining operations has had a significant impact on former workers, particularly in economic, social, and psychological aspects. This study aims to analyze the resilience of former mine workers in coping with life changes after losing their jobs. A qualitative approach was used, involving in-depth interviews with 12 informants who were selected based on variations in age, work history, and post-closure employment conditions. The findings indicate that most informants were able to adapt by seeking new jobs, starting small businesses, and adopting a frugal lifestyle to manage limited income. Socially, the majority of former workers managed to reintegrate into the community through participation in groups such as farmer associations and youth organizations, which not only strengthened social bonds but also opened new economic opportunities. Psychologically, seven informants successfully managed stress and anxiety through positive activities, while four others continued to struggle with emotional distress, with two experiencing severe stress requiring prolonged adjustment. Key factors supporting resilience include strong family and peer support, openness to change, and the ability to formulate strategies for overcoming economic and social challenges. This study emphasizes that resilience is not merely about enduring hardship but also about rebuilding stability and fostering personal growth amid changing post-mining conditions.